2013
DOI: 10.1007/s11255-013-0447-6
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related tubulointerstitial nephritis presenting with psychiatric manifestations and skin lesions

Abstract: We describe a 21-year male with mood disorder on lithium therapy and psoriasis-like skin lesions presenting with rapidly progressive renal failure. The kidney biopsy showed acute tubulointerstitial nephritis with immunoglobulin G4-positive plasma cell infiltration. He was started on oral steroids with a provisional diagnosis of IgG4-related tubulointerstitial nephritis. All dermatological, psychiatric and renal manifestations dramatically improved, and he was taken off lithium. He had a relapse of his psychiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The reported case and ours are characterized by infiltration of plasma cells, some of which bore IgG4, and deposition of IgG4 in the vascular endothelial cells. Notably, these and our own cases developed psoriasis‐like eruption after long‐standing sclerosing cholangitis and/or sclerosing kidney . As the frequency of psoriasis is generally high, it remains to be elucidated whether IgG4‐RD and psoriasis are pathologically related or simply coincidental.…”
Section: Classification Of Igg4‐related Diseasementioning
confidence: 74%
See 1 more Smart Citation
“…The reported case and ours are characterized by infiltration of plasma cells, some of which bore IgG4, and deposition of IgG4 in the vascular endothelial cells. Notably, these and our own cases developed psoriasis‐like eruption after long‐standing sclerosing cholangitis and/or sclerosing kidney . As the frequency of psoriasis is generally high, it remains to be elucidated whether IgG4‐RD and psoriasis are pathologically related or simply coincidental.…”
Section: Classification Of Igg4‐related Diseasementioning
confidence: 74%
“…A couple of cases have shown that patients with IgG4‐RD develop multiple hyperkeratotic erythematous plaques indistinguishable from chronic plaque psoriasis . There were typical histological findings, but plasma cells infiltrated perivascularly .…”
Section: Classification Of Igg4‐related Diseasementioning
confidence: 99%
“…This creates significant potential pitfalls. For example, failure to utilize stringent diagnostic criteria resulted in a recent attempt at classification of cutaneous IgG4‐RD that incorporated many spurious entities, including a lithium‐induced exacerbation of incidental psoriasis (not biopsied), cases that were never evaluated for the presence of IgG4‐bearing plasma cells, and mimetic cases wherein the diagnosis of IgG4‐RD was ruled out . We now address these diagnostic pitfalls by classification of IgG4‐RD mimics based on degree of clinicopathologic similarity (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1 Psoriasis-like eruptions have been reported in only two cases, which were complicated with sclerosing cholangitis or tubulointerstitial nephritis. 5,6 To our knowledge, patients described above in case 1 and case 2 are the first two reported cases of GPP complicated by IgG4-RD.…”
mentioning
confidence: 87%
“…IgG4‐positive plasma cells or IgG4 can indirectly lead to psoriasis‐like eruptions, hypergammaglobulinaemic purpura, unspecified maculopapular or erythematous eruptions, urticarial vasculitis, and ischaemic digit as secondary skin manifestations . Psoriasis‐like eruptions have been reported in only two cases, which were complicated with sclerosing cholangitis or tubulointerstitial nephritis . To our knowledge, patients described above in case 1 and case 2 are the first two reported cases of GPP complicated by IgG4‐RD.…”
mentioning
confidence: 89%